Microbes as Master Immunomodulators: Immunopathology, Cancer and Personalized Immunotherapies - Lérias, Joana R.; Paraschoudi, Georgia; de Sousa, Eric; Martins, João; Condeço, Carolina; Figueiredo, Nuno; Carvalho, Carlos; Dodoo, Ernest; Castillo-Martin, Mireia; Beltrán, Antonio; Ligeiro, Dário; Rao, Martin; et al. (Frontiers in Cell and Developmental Biology, 2020)
The intricate interplay between the immune system and microbes is an essential part of physiological homeostasis in health and disease. Immunological recognition of commensal microbes, such as bacterial species resident in the gut or lung as well as dormant viral species, i.e., cytomegalovirus (CMV) or Epstein-Barr virus (EBV), in combination with a balanced immune regulation, is central to achieve immune-protection. Emerging evidence suggests that immune responses primed to guard against commensal microbes may cause unexpected pathological outcomes, e.g. chronic inflammation and/or malignant transformation. Furthermore, translocation of immune cells from one anatomical compartment to another, i.e., the gut-lung axis via the lymphatics or blood has been identified as an important factor in perpetrating systemic inflammation and tissue destruction as well as modulating host-protective immune responses. We present in this review immune response patterns to pathogenic as well as non-pathogenic microbes and how these immune-recognition profiles affect local immune responses or malignant transformation. We discuss personalised immunological therapies which, directly or indirectly, target host biological pathways modulated by antimicrobial immune responses.